Targeting Epicardial/Pericardial Adipose Tissue in Cardiovascular Diseases: A Novel Therapeutic Strategy - Yue Ding; Fang Lin; Zhongmin Liu; Xiaohui Zhou; Xiaoting Liang (Reviews in Cardiovascular Medicine)
Cardiovascular diseases (CVDs) remain a global health concern, prompting ongoing research into novel contributors to their pathogenesis. Due to the proximity of the coronary arteries and the myocardium in epicardial adipose tissue (EAT) and pericardial adipose tissue (PAT), these tissues have emerged as key areas of interest for their potential influence on cardiac function and vascular health. This review synthesizes current research on the physiological and biological characteristics of EAT and PAT, exploring their composition and clinical measurement approaches. The roles of EAT and PAT in coronary artery disease (CAD), atrial fibrillation, and heart failure are discussed, and the contributions of EAT and PAT to these cardiovascular conditions are highlighted alongside their potential as therapeutic targets.